Cattle in ritual practice and iconography in Bronze Age Cyprus - Webb, Jennifer M. (Journal of Greek Archaeology, 2017)
The difficulties involved in identifying the archaeological remnants of belief systems have been widely discussed. In many or even most instances, the material correlates of ritual action are likely to have left non-durable (myth, dancing, prayer, prophecy, libations) or non-diagnostic traces. Issues of recognition are thus fundamental to any discussion of the meaning and function of images and symbols and the artefacts on which they are inscribed. One approach – and that adopted here – is to limit the investigation to materials recovered from ritual contexts (where these can be identified) or otherwise of obvious ritual function or content, so that their operational role may be most clearly understood.